A Retrospective Cohort Study of Multiple Immune-Related Adverse Events and Clinical Outcomes Among Patients With Cancer Receiving Immune Checkpoint Inhibitors. (23rd September 2022) - Hata, Hiroki; Matsumura, Chikako; Chisaki, Yugo; Nishioka, Kae; Tokuda, Misaki; Miyagi, Kazuyo; Suizu, Tomoki; Yano, Yoshitaka
Background and Objectives: Immune checkpoint inhibitors (ICIs) are effective in various types of cancer and cause immune-related adverse events (irAEs). The occurrence of irAEs is associated with improved survival outcome. We investigated the association between the occurrence of irAEs and overall survival (OS) and progression free survival (PFS), and the risk factors for the development of irAEs, in patients with non–small-cell lung cancer (NSCLC), gastric cancer (GC) and melanoma (MM) treated with ICIs. Methods: This was a retrospective observational cohort study, and the data were taken from inpatients in a hospital. OS and PFS were compared among patients with different numbers of irAEs. Log-rank test and Cox regression and logistic regression analysis were applied, and details of irAEs characteristics were summarized. Results: We obtained data from 200 patients. The major tumor types were NSCLC, GC, and MM. Median OS and PFS in all patients were 9.3 and 3.5 months, respectively. Patients without irAEs tended to have shorter OS or PFS compared with those with a single irAE or multi-system irAEs. Covariate analysis suggested that age (≥75 years), albumin (≥3.5 g/dL) and smoking history were significant for increased occurrence of irAEs. Pneumonitis and thyroiditis tended to occur frequently in patients with NSCLC and MM. The irAE grade was ≤2 in 67.3% of all irAEs, and days of irAEs onset varied. Conclusion: We observed patients with irAEs tended to have better OS or PFS in patients with various types of cancers treated with ICIs. We suggest that ICIs should be used appropriately by continuously monitoring the irAEs.